2012
DOI: 10.4161/onci.20663
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin

Abstract: Vaccines that generate Ag-specific CD8+ T-cell responses of appropriate quality, magnitude and duration are highly desirable. The ability of mTOR to regulate CD8+ T-cell functional differentiation must be exploited for clinical benefit. In a recent paper, we report that varying the regimen of rapamycin administration regulates viral vaccine-induced CD8+ T-cell responses for tumor immunity. These observations validate the use of rapamycin in vaccination strategies and demonstrate the efficacy of memory CD8+ T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Mouse models for the study of the effect of rapamycin on breast cancer [ 69 ] and melanoma [ 70 ] have been described and have proved useful for determining biomarkers. Establishing the optimal dose of rapamycin will be critical to its efficacy as its beneficial effects must be balanced against its immunosuppressive properties, and achieving the optimal dose has been likened to adjusting a rheostat [ 71 ].…”
Section: Reviewmentioning
confidence: 99%
“…Mouse models for the study of the effect of rapamycin on breast cancer [ 69 ] and melanoma [ 70 ] have been described and have proved useful for determining biomarkers. Establishing the optimal dose of rapamycin will be critical to its efficacy as its beneficial effects must be balanced against its immunosuppressive properties, and achieving the optimal dose has been likened to adjusting a rheostat [ 71 ].…”
Section: Reviewmentioning
confidence: 99%
“…MTOR inhibitors are widely used to suppress a rejection response by the immune system in organ transplantation [ 12 ]. Paradoxically, mTOR inhibitor was recently shown to potentiate immune response by generating memory CD8+ T-cells in a dose- and duration-dependent manner [ 13 16 ]. Li et al [ 17 ] reported that a short course of high-dose, instead of low-dose rapamycin, generated memory CD8+ T-cell responses, and afforded more durable protection against tumor compared with persistent administration of either low or high dose.…”
Section: Introductionmentioning
confidence: 99%
“…Ovalbumin-specific αβ T lymphocytes exposed to microspheres coated with an ovalbumin-derived peptide plus co-stimulatory CD80 molecules (or with anti-CD3/anti-CD28 antibodies) in the presence of rapamycin exhibited improved memory and antitumor functions in vivo than T cells of the same type activated in the presence of interleukin (IL)-12 [85-87]. Along similar lines, rapamycin has been shown to enhance tumor-targeting CD8 + T-cell memory responses elicited by a poxviral anticancer vaccine in mice [88, 89]. Such an immunostimulatory activity was observed only when rapamycin was administered in a high-dose short therapeutic course, as opposed to both a single, low-dose course as well as prolonged treatment schedules [88, 89].…”
mentioning
confidence: 99%
“…Along similar lines, rapamycin has been shown to enhance tumor-targeting CD8 + T-cell memory responses elicited by a poxviral anticancer vaccine in mice [88, 89]. Such an immunostimulatory activity was observed only when rapamycin was administered in a high-dose short therapeutic course, as opposed to both a single, low-dose course as well as prolonged treatment schedules [88, 89]. Of note, rapamycin has also been shown to increase the yield and effector functions of human γδ T cells activated in vitro with isopentenyl pyrophosphate plus recombinant IL-2 [90].…”
mentioning
confidence: 99%